Controlling Magnetic and Optical Properties of the van der Waals Crystal CrCl3−xBrx via Mixed Halide Chemistry. Issue 25 (2nd May 2018) - Abramchuk, Mykola; Jaszewski, Samantha; Metz, Kenneth R.; Osterhoudt, Gavin B.; Wang, Yiping; Burch, Kenneth S.; Tafti, Fazel
Abstract: Magnetic van der Waals (vdW) materials are the centerpiece of atomically thin devices with spintronic and optoelectronic functions. Exploring new chemistry paths to tune their magnetic and optical properties enables significant progress in fabricating heterostructures and ultracompact devices by mechanical exfoliation. The key parameter to sustain ferromagnetism in 2D is magnetic anisotropy—a tendency of spins to align in a certain crystallographic direction known as easy‐axis. In layered materials, two limits of easy‐axis are in‐plane ( XY ) and out‐of‐plane (Ising). Light polarization and the helicity of topological states can couple to magnetic anisotropy with promising photoluminescence or spin‐orbitronic functions. Here, a unique experiment is designed to control the easy‐axis, the magnetic transition temperature, and the optical gap simultaneously in a series of CrCl3− x Br x crystals between CrCl3 with XY and CrBr3 with Ising anisotropy. The easy‐axis is controlled between the two limits by varying spin–orbit coupling with the Br content in CrCl3− x Br x . The optical gap, magnetic transition temperature, and interlayer spacing are all tuned linearly with x . This is the first report of controlling exchange anisotropy in a layered crystal and the first unveiling of mixed halide chemistry as a powerful technique to produce functional materials for spintronic devices. Abstract : Controlling the magnetic anisotropy in layered materials is a major progress necessary for the fabrication of the next‐generation 2D magneto‐optical devices. Such a control is achieved by mixing halide species in transition‐metal mixed halides where the spin–orbit coupling tunes the magnetic anisotropy. The mixed halide chemistry can be generalized to all transition metals.